EFFECTS OF COMPUTER ASSISTED INSTRUCTIONAL PACKAGE ONACHIEVEMENT AND INTEREST OF SENIOR SECONDARY SCHOOLSTUDENTS IN MATHEMATICS IN BIDA METROPOLIS, NIGER STATE,NIGERIA. - Gimba, R. W.; Hassan, A. A.; Abdulrahman, M.; Bashir, A. (Sokoto Educational Review, 2014)
This study compared the effects of the researcher designed Computer Assisted Instruction (CAI) package on achievement and interest of senior secondary school students in set theory to the traditional teaching method. The study was carried out in Bida Metropolis. Two senior secondary schools were purposively chosen because of the availability of computers in these schools. A sample of one hundred and nine (109) SSI students was involved in the study. The design used was a quasi-experimental design. Two intact classes were used; four research questions and four hypotheses guided the study, while Mean, standard deviation and t-test were used to test the hypotheses at 0.05 level o f significant. The result revealed that the mean and standard deviation of the post-test achievement score of experimental and control groups are 60.25 and Standard Deviation 0.12, and 31.15 and Standard Deviation 0.10 respectively in favour of the experimental group and the interest inventoiy score of experimental and control groups are 58.43 and Standard Deviation 0.18, and 32.23 and Standard Deviation 0.23 respectively in favour of the experimental group. The study revealed no significant difference in the mean achievement and interest scores of male and female students taught using CAT package. Some recommendations were made among which is mathematics teachers should include the use of computer assisted instructional package as one of the strategies to be employed in classroom teaching and learning.